A reconstruction of the mid-to late Pleistocene plant community along the southwestern coast of South Africa using phytolith evidence - Mann, Nicole Jean (Department of Archaeology, 2018)
The sites of Elandsfontein (EFT) and Duinefontein (DFT) preserve important records of mid-Pleistocene human occupation along South Africa's southwestern coast. In addition to human fossils in the case of EFT, both sites have produced extensive collections of artefacts and faunal remains. Analyses of the latter have provided the broad environmental contexts for mid-Pleistocene human occupation along this coast. Recently, research into landscape use by mid-Pleistocene human populations at EFT and DFT has highlighted the need for more precise palaeoenvironmental data for the region. In response to this need, I analysed plant phytoliths extracted from sediments sampled at EFT and DFT. The results of this analysis are reported and interpreted in this thesis. To assist with the interpretation of the EFT and DFT phytolith assemblages, I established a modern phytolith reference collection. In addition, pre-existing phytolith collections were examined and literature was consulted. Phytoliths extracted from modern and mid-Pleistocene aged sediments sampled at different localities at EFT and DFT were identified and tallied to determine vegetation composition during the middle Pleistocene. Distinctions were made between "grassier" and "more woody" samples. Analyses of modern plant samples confirmed that grass species produced abundant phytoliths, whereas the majority of dicotyledons did not produce diagnostic morphotypes. Phytoliths belonging to grass species currently growing in the region were identified in the modern sediment samples, as were non-grass phytoliths that included those from woody dicotyledonous and monocotyledon plants. The majority of the mid-Pleistocene sediment samples from EFT produced varying proportions of grass, woody dicotyledon, monocotyledon, sedge and palm type phytoliths which are characteristic of cool-season growing landscapes. In comparison to EFT, the late mid- Pleistocene sediment samples from DFT contained fewer phytoliths. These results suggest that the conditions at DFT were either not conducive to the preservation of phytoliths or that the vegetation was sparse and/or did not produce abundant phytoliths. Where sufficient phytoliths were preserved, assemblages suggested landscapes similar to that of EFT. In summary, analyses suggest that during the middle to late Pleistocene, a heterogeneous vegetation community, consisting primarily of C₃ grasses, woody dicotyledons and other monocotyledonous plants existed along South Africa's southwest coast. Furthermore, results support the longterm presence of the winter rainfall zone in the region. This study demonstrates the potential of phytolith analysis as an important proxy in determining the composition of palaeo-vegetation communities in South Africa. Although there were limitations that necessitated the broad classification of phytolith groups, the study nevertheless provided more precise information, particularly about mid-Pleistocene vegetation structure, that was not previously available.